Risks associated with suspected dysphagia in infants admitted to a neonatal intensive care unit in a South African public hospital - Jacoline Schoeman; Alta Kritizinger (South African Medical Association, 2017)
Background. The prevalence of neonatal dysphagia is increasing, as medical advances contribute to the survival of critically ill and preterm infants. Additional factors such as low birth weight (LBW), gastro-oesoephageal reflux disorder, failure-to-thrive (FTT), and HIV may increase the complexity of dysphagia symptoms. Knowledge of context-specific risk factors for dysphagia may lead to an effective pathway of diagnosis and management in vulnerable neonates. Objective. To describe the feeding characteristics and categories of underlying medical conditions in infants of gestational age 24 - 42 weeks. Methods. The study was a retrospective review of 231 purposively selected medical and speech-language therapy records. Participants had a mean stay of 28.5 days in a neonatal intensive care unit in a peri-urban public hospital and were referred for a swallowing and feeding assessment. An existing seven-category framework for the classification of suspected dysphagia was used. Results. Most participants (90.0%) presented with multiple medical conditions. Underlying neurological conditions (48.5%) and feeding difficulties secondary to systemic illness (65.8%) contributed mostly to suspected dysphagia in the sample. It was found that 71.0% of infants presented with feeding difficulties secondary to other conditions such as LBW and prematurity, highlighting the need for an expanded dysphagia classification framework. Conclusion. The results concur with the outcomes of previous studies and confirm the need for a unique classification framework in South Africa. Dysphagia is a complex condition and frequently cannot be attributed to a single risk factor.